2012
DOI: 10.1111/j.1742-1241.2012.03013.x
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic use: do parents act differently for their children?

Abstract: On the whole, parents did to their children what they would do for themselves, but to a lesser extent. Parents' better knowledge and attitudes will lead to more appropriate use of antibiotics for their children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
45
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(52 citation statements)
references
References 22 publications
(29 reference statements)
6
45
1
Order By: Relevance
“…This is in corroboration with a large body of previous similar surveys around the world [1], [21], [34], [38], [39]. Interestingly, other studies reported different diseases and symptoms as major reasons for self-treatment with antibiotics, such as tonsillitis [32], upper respiratory tract infections [40], common cold [22], [31], fever [25], [41], and cough [28], [42], [43].…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This is in corroboration with a large body of previous similar surveys around the world [1], [21], [34], [38], [39]. Interestingly, other studies reported different diseases and symptoms as major reasons for self-treatment with antibiotics, such as tonsillitis [32], upper respiratory tract infections [40], common cold [22], [31], fever [25], [41], and cough [28], [42], [43].…”
Section: Discussionsupporting
confidence: 87%
“…Most of the respondents knew that antibiotics are not effective for cold, but erroneously believed that antibiotics can be used for sore throat, flu, and fever. In a large telephone survey among adults in Hong Kong, 91% had heard the term of antibiotic resistance [25], and in the general public in Malaysia respectively about 59% and 67.2% knew that overuse of antibiotics could cause antibiotic resistance and incorrectly thought that antibiotics are also used to treat viral infections [27]. A survey on adults in the United Kingdom showed that 38% did not know that antibiotics do not work on most coughs and colds [17].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Parents reported more satisfaction when they knew and trusted their clinician and felt the clinician knew their family (Al‐Dossari, ; Alili‐Idrizi et al., ; Alkhaldi et al., ; Brookes‐Howell et al., ; Cabral et al., ; Chinnasami et al., ; Ecker et al., ; Panagakou et al., ; Rousounidis et al., ; Salazar et al., ; Zyoud et al., ). However, in three of the studies, parents felt that the clinician did not know their child or discuss their child's health with them, resulting in a feeling of lack of trust in the clinician and reduced compliance from parents (Alkhaldi et al., , Dwibedi et al., ; Wun et al., ). One US study identified some parents felt clinicians were rude to them if they asked questions about their child's illness (Dwibedi et al., ), preventing them from doing so and from interacting with healthcare professionals.…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown the generally short timespan between the onset of fever in children and the parents seeking medical care, thus hampering the diagnosis of the origin of fever (Kitt et al, ). The parental concern regarding their children’s symptoms or the false beliefs surrounding fever (such as the belief that fever can lead to complications, including fever convulsions, brain damage, mental problems, or even death) (de Bont et al, ; Langer et al, ; Villarejo‐Rodríguez & Rodríguez‐Martín, ), the lack of knowledge on the management of fever (Ertmann et al, ; Kitt et al, ), or the tendency to request antibiotics for the treatment of childhood fever (de Bont et al, ; Wun, Lam, Lam, & Sun, ), have all been suggested as reasons for the haste parents frequently display in seeking medical assistance for their child.…”
mentioning
confidence: 99%